COVID-19 Reinfection or Relapse: Case Series - Sarma, Rinki; Kumar, Balbir; Garg, Rakesh; Kumar, Brajesh (Asian Pacific Journal of Cancer Care, 2022)
One-time reinfection with SARS-Cov-2 does not warranty of immunity against reinfection due to various possible reasons for this like waning immunity or high viral load or an immunocompromised state. Cases of reinfection have been reported from many countries in the world, here in this case series we are sharing the experience of three cases of reinfection from India. Two of them were old with multiple comorbidities and one is a young patient with no comorbidity. All three-patient got reinfected less than two months.